The Paradox of the Sufi Sultanate: Charismatic Scaffolding and Epistemic Erasure in Islamic Statecraft - Hidayat, Muhammad Syaiful Bahri; Ulum, Muhammad Nashrul (An-Nur International Journal of Islamic Thought, 2025)
History records recurring instances where Sufi brotherhoods transitioned into territorial states, notably in the Safavid Empire, the Sokoto Caliphate, and North African resistance movements. However, current scholarship often conflates the mystical identity of founders with the administrative reality of these polities, assuming a continuity of "Sufi governance" that empirical evidence contradicts. This study employs a comparative historical analysis to deconstruct the "Sufi Sultanate" as a political typology. By juxtaposing the Naqshbandī fiscalization in Central Asia, the Qādirī mobilization in West Africa, and the Sanūsī tribalization in Libya, the research isolates the structural mechanisms of state formation. Findings reveal a consistent process of "epistemic erasure," where the murshid-murīd bond—essential for initial mobilization—is systematically dismantled or "transubstantiated" into legal-rational or patrimonial authority once power is consolidated. Whether through the imposition of sharī‘a courts or the bureaucratization of waqf endowments, the "Sufi" infrastructure serves merely as revolutionary scaffolding. This article challenges the concept of "Sufi Exceptionalism," arguing that the "Sufi State" is inherently transient and inevitably yields to conventional Islamic statecraft to ensure political survival.